Climate Change and Social Inequality: Vulnerabilities of Marginalised Communities - Shashank (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Climate change represents one of the most profound and pressing challenges facing humanity in the twenty-first century. Its impacts are diverse, ranging from rising global temperatures and sea-level rise to increased frequency and severity of extreme weather events. While climate change affects all regions and populations to varying degrees, its consequences are not experienced equally. Marginalised communities, often encompassing groups defined by ethnicity, socioeconomic status, geography, and other social determinants, are disproportionately vulnerable to the adverse effects of climate change. The intersection of climate change and social inequality reveals significant disparities in exposure to climate risks, capacity to adapt, and access to resources for resilience, thereby reinforcing and exacerbating existing inequalities. The present paper explores the vulnerabilities of marginalised communities in the face of climate change, examining the multifaceted nature of these risks and highlighting the imperative for equitable and inclusive climate policies. Understanding the vulnerabilities of marginalised communities requires a contextual analysis of both climate-related hazards and the socio-political conditions that shape exposure and adaptive capacity. Climate change hazards such as heat waves, floods, droughts and storms pose physical threats that can lead to loss of life, livelihoods, and property. However, the extent to which communities suffer from these hazards depends heavily on their resilience, which is mediated by underlying social, economic and political factors. Marginalised groups often inhabit geographically vulnerable areas, such as floodplains, coastal zones, or arid lands, due to historical processes of dispossession, discrimination, and exclusion from more secure living spaces. For instance, low-income populations in urban centres frequently reside in informal settlements characterized by inadequate infrastructure, poor housing quality and insufficient sanitation facilities, rendering them particularly susceptible to climate-induced disasters.